Analytical methods for honeybee venom characterization - Iouraouine El Mehdi; Soraia I Falcão; Saïd Boujraf; Harandou Mustapha; Maria G Campos; Miguel Vilas-Boas (Wolters Kluwer Medknow Publications, 2022)
The discovery of new drugs has benefited significantly from the development of research in venomics, increasing our understanding of the envenomation processes. It has been previously reported that honeybee venom (HBV) exhibits several pharmacological activities such as anti-inflammatory, antibacterial, antimutagenic, radioprotective, and anticancer activity and may inclusively act as a complementary treatment for SARS-CoV-2. It composition consists mainly on melittin, phospholipase A2, and apamin but other constituents such as hyaluronidase, mast cell degranulating peptide and secapin are also relevant for its bioactivity. However, and because HBV is not officially recognized as a drug, until now, the international community did not establish quality standards for it. To uncover its exact composition, and boost the discovery of HBV-derived drugs, a significant number of techniques were developed. In this review, a relevant overview of the so far published analytical methods for HBV characterization is organized with the aim to accelerate its future standardization. The literature search was performed within PubMed, Google Scholar, and Science Direct by selecting specific documents and exploring HBV evaluation.